Sensorys Characteristics of Gandaria (Bouea macrophylla Griff.) Jelly Drink with Variation of Guar Gum Concentration - Gilian Tetelepta (Jurnal Agrosilvopasture-Tech, 2022)
Gandaria is a local plant from Maluku which is a combination of sour and sweet tastes so it has the opportunity to be processed into jelly drinks. A jelly drink is a solid drink in the form of a gel that is affected by a gelling agent such as guar gum. The objective of this study was to determine the appropriate concentration of guar gum for the gandaria jelly drink. The research design was using the single factor Completely Randomized Design with guar gum concentrations of 0.1%, 0.2%, 0.3%, and 0.4%. The sensory properties tested were color, taste, aroma, texture, suction power, and overall. The results showed that the gandaria jelly drink with a guar gum concentration of 0.2% had the best level of acceptance with a hedonic value for color 3.1, taste 2.7, aroma 2.7, texture 3.2, suction power 3.1, and overall, 3.4 which all included criteria approaching like. The hedonic quality value of color is 2.8 (close to slightly yellow), taste is 2.3 (slightly gandaria taste), aroma 2,1 (slightly gandaria flavor), texture is 2.4 (slightly chewy), and suction power is 3.1 (easy to suck).